Analisis Sistem Akuntansi Penggajian dan Pengupahan pada PT X - Krisdayanti, Merin; Kustiningsih, Nanik (Universitas Nahdlatul Ulama Surabaya, 2021)
The accounting information system for contracts and wages is very important for a company which can assist in making decisions and archieving the implementation of payroll and wages for employees. The goal is to be able to find out how the implementation of the accounting system for payroll and wages at PT. X. This type of research used in this research is descriptive research using data analysis methods, namely qualitative data analysis. This study aims to identify and analyze the payroll and wage accounting information system at PT. X. The results of this analysis indicate the payroll and wages accounting information system at PT. X which is still not supportive, as well as the lack of supervision on the attendance list of employees, this shows the weakness that accours in the company PT. X.